High-entropy alloy water electrolysis hydrogen evolution material and preparation method thereof
Patent Information
- Application Number
- CN202410100023.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-24
AI Technical Summary
然而该催化材料大电流密度下性能不佳,无法满足工业级电解水需求,且稳定性较差
[0019] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects: (1) FeCoNiCrPt high-entropy alloy thin films are rapidly prepared by pulsed laser deposition. The process is simple, the preparation speed is fast, the cost is low, and the film has a large specific surface area and strong film-substrate bonding force, which significantly improves the catalytic performance under high current density and realizes industrial-grade water electrolysis for hydrogen production; (2) Vacancies and lattice strain are formed on the surface of the high-entropy alloy thin film by electrochemical etching treatment, which optimizes atomic coordination and electronic structure, significantly reduces the overpotential of hydrogen evolution reaction, and realizes the preparation of low-cost, high-stability, high-efficiency high-entropy alloy thin film catalytic materials; (3) The alloy has excellent performance in the full pH range and under high current density, and has excellent operating stability in anion exchange membrane electrolyzers.
Smart Images

Figure CN117966191B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-entropy alloy material and its preparation method, and more particularly to a high-entropy alloy catalytic hydrogen evolution material for water electrolysis and its preparation method. Background Technology
[0002] Hydrogen energy is a key component of my country's energy structure transformation. Renewable energy-driven water electrolysis hydrogen production technology offers a powerful solution for "green hydrogen" production due to its high purity and environmental friendliness. However, the current challenge in this field lies in developing catalytic materials that combine high activity, universal pH compatibility, and sustainability to meet the requirements of industrial applications.
[0003] Transition metals such as iron, cobalt, and nickel possess incompletely filled d orbitals, exhibiting excellent catalytic activity and low cost, and are currently widely used in the preparation of catalytic materials for the hydrogen evolution reaction in water electrolysis. High-entropy alloys possess unique high-entropy effects, lattice distortion effects, hysteresis diffusion effects, and "cocktail" effects, offering potential advantages such as high catalytic activity and excellent cycle stability as catalytic materials for the hydrogen evolution reaction. Pulsed laser deposition (PLD) is a type of physical vapor deposition method. It is simple to operate, technically flexible, has a high deposition rate, and is virtually unrestricted in terms of the types of deposition materials and substrates, making it widely used for depositing metals, ceramics, ferroelectric materials, and superconducting thin films. However, a drawback of this technology is the high surface roughness of the resulting films, which adversely affects their optical, electrical, and magnetic properties. However, it offers significant advantages for specialized applications such as catalysis and sensing. Furthermore, the film-substrate bonding of materials prepared by PLD is much stronger than that of supported catalytic materials, promising for achieving industrial-scale water electrolysis at current densities and longer cycle durability. However, there are few reports on the preparation of high-entropy alloy thin-film water electrolysis catalytic materials using this technology.
[0004] Chinese patent application CN114855187A discloses a high-current electrocatalytic water splitting hydrogen production catalyst material. A metal precursor is obtained through a hydrothermal reaction for 1–10 hours, followed by high-temperature treatment for 20 minutes–8 hours to obtain the catalyst material powder. The process involves a current density of 500 mA / cm². -2 The samples with the best performance were found to have overpotentials of 152 mV (pH=14) and 419 mV (pH=7). However, the preparation process of this method is relatively complex and time-consuming, and its performance under high current is still difficult to meet the needs of industrial production.
[0005] Chinese patent application CN114836780A discloses a hexavalent high-entropy foam catalyst for hydrogen production via water electrolysis, obtained by electrodepositing metal salts corresponding to Ni, Fe, Cu, Co, Mo, and Pt onto a Ni sheet. However, this catalyst exhibits poor performance at high current densities, failing to meet the requirements of industrial-grade water electrolysis, and also suffers from poor stability. Summary of the Invention
[0006] Purpose of the invention: The purpose of this invention is to provide a high-entropy alloy catalytic hydrogen evolution material for water electrolysis with high catalytic activity, high stability, and full pH adaptability, as well as its preparation method;
[0007] The second objective of this invention is to provide a method for preparing the aforementioned high-entropy alloy catalytic hydrogen evolution material for water electrolysis.
[0008] Technical solution: The high-entropy alloy electrolytic hydrogen evolution catalyst material of the present invention comprises a conductive substrate material and a high-entropy alloy thin film deposited on the surface of the conductive substrate material; the high-entropy alloy thin film has the chemical formula (FeCoNiCr) based on the molar percentage of each atom. 100-x Pt x , where 10≤x≤40.
[0009] The preparation method of the above-mentioned high-entropy alloy electrolysis hydrogen evolution catalyst includes the following steps:
[0010] (1) Weigh the Fe, Co, Ni, Cr and Pt metal raw materials according to the molar percentage of each atom;
[0011] (2) The metal raw materials from step (1) are subjected to electric arc melting to obtain (FeCoNiCr). 100-x Pt x The alloy ingot is cut and its surface is polished to obtain (FeCoNiCr). 100-x Pt x Target material;
[0012] (3) Utilization (FeCoNiCr) 100-x Pt x The target material (FeCoNiCr) was deposited on a conductive substrate using pulsed laser deposition. 100-x Pt x High-entropy alloy thin films;
[0013] (4) The obtained high-entropy alloy film is electrochemically etched, washed and dried to obtain the high-entropy alloy water electrolysis hydrogen evolution catalyst material.
[0014] In step (2), argon is used as the protective atmosphere in the arc melting method.
[0015] In step (3), the laser wavelength used in the pulsed laser deposition method is 1064nm, and the protective atmosphere is argon; the substrate size used in the pulsed laser deposition method is Φ5-12mm; the deposition time of the pulsed laser deposition method is 10-20min; preferably 15-20min.
[0016] In step (4), the medium for electrochemical etching is an acidic solution; the acidic solution is at least one of H2SO4, HNO3, and HCl.
[0017] In step (4), the electrochemical etching adopts the constant potential etching method, the applied voltage is -0.245-1.40V (vs. SCE), the etching time is 0-1200s, and the electrochemical etching temperature is room temperature.
[0018] Invention Principle: Pulsed laser deposition (PLD) can rapidly prepare high-entropy alloy thin film materials. On one hand, the cost of high-entropy alloys containing noble metals can be significantly reduced by adding transition metal elements such as Fe, Co, Ni, and Cr. On the other hand, by utilizing the properties of these elements, active metals can be selectively removed in acidic solutions, generating a large number of atomic vacancies in situ, increasing the number of dangling bonds, and optimizing the water molecule adsorption process. By controlling the electrochemical etching voltage and time, the degree of lattice strain caused by vacancies can be altered, optimizing the type of atomic coordination and the length of coordination bonds. Density functional theory calculations show that the presence of lattice strain significantly promotes both the Volmer and Heyrovsky processes of the hydrogen evolution reaction. In summary, electrochemical etching creates vacancies and lattice strain on the surface of high-entropy alloy thin films, thereby improving their catalytic performance in the hydrogen evolution reaction.
[0019] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects: (1) FeCoNiCrPt high-entropy alloy thin films are rapidly prepared by pulsed laser deposition. The process is simple, the preparation speed is fast, the cost is low, and the film has a large specific surface area and strong film-substrate bonding force, which significantly improves the catalytic performance under high current density and realizes industrial-grade water electrolysis for hydrogen production; (2) Vacancies and lattice strain are formed on the surface of the high-entropy alloy thin film by electrochemical etching treatment, which optimizes atomic coordination and electronic structure, significantly reduces the overpotential of hydrogen evolution reaction, and realizes the preparation of low-cost, high-stability, high-efficiency high-entropy alloy thin film catalytic materials; (3) The alloy has excellent performance in the full pH range and under high current density, and has excellent operating stability in anion exchange membrane electrolyzers. Attached Figure Description
[0020] Figure 1 (FeCoNiCr) was prepared as described in Example 1. 80 Pt 20 GIXRD patterns of high-entropy alloy thin films as a function of etching time;
[0021] Figure 2 (FeCoNiCr) was prepared as described in Example 1. 80 Pt 20 SEM images of the surface and cross-section of a high-entropy alloy thin film as a function of etching time;
[0022] Figure 3Preparation of pristine (FeCoNiCr) for Example 1 80 Pt 20 TEM and SAED images of high-entropy alloy thin films;
[0023] Figure 4 Preparation of FeCoNiCr after etching for 300 s as in Example 1 80 Pt 20 TEM images and vacancy analysis diagrams of high-entropy alloy thin films;
[0024] Figure 5 Preparation of raw (FeCoNiCr) and (after etching for 300 s) samples for Example 1. 80 Pt 20 GPA image of high-entropy alloy thin film;
[0025] Figure 6 For Example 1, FeCoNiCr was prepared with different etching times. 80 Pt 20 HER linear sweep voltammetry curves of high-entropy alloy thin films in 1.0 MKOH electrolyte;
[0026] Figure 7 For etching 300s (FeCoNiCr) 80 Pt 20 Chrono-voltage curves of alkaline HER in high-entropy alloy thin films;
[0027] Figure 8 The etching depth for 300 seconds (FeCoNiCr) in Example 1 is [missing information]. 80 Pt 20 The chronovoltammetric curves of alkaline HER were tested in an assembled flowable anion exchange membrane electrolyzer.
[0028] Figure 9 For Example 1, FeCoNiCr was prepared with different etching times. 80 Pt 20 HER linear sweep voltammetry curves of high-entropy alloy thin films in 0.5 M H₂SO₄ electrolyte;
[0029] Figure 10 The etching depth for 300 seconds (FeCoNiCr) in Example 1 is [missing information]. 80 Pt 20 When high-entropy alloy thin films are used as HER catalysts in water electrolysis, they achieve a 10 mA / cm² reaction in a 0.5 M H₂SO₄ electrolyte. -2 Timing voltage curve;
[0030] Figure 11 For Example 1, FeCoNiCr was prepared with different etching times. 80 Pt 20HER linear sweep voltammetry curves of high-entropy alloy films in 1.0M PBS electrolyte;
[0031] Figure 12 The etching depth for 300 seconds (FeCoNiCr) in Example 1 is [missing information]. 80 Pt 20 When high-entropy alloy films are used as HER catalysts in water electrolysis, they achieve a 10 mA cm⁻¹ in 1.0 M PBS electrolyte. -2 Timing voltage curve;
[0032] Figure 13 In Example 2, (FeCoNiCr) 80 Pt 20 Polarization curves of high-entropy alloy thin films in 0.5M H2SO4 electrolyte;
[0033] Figure 14 Example 2: (FeCoNiCr) samples were prepared by etching at different potentials for 500 s. 80 Pt 20 HER linear sweep voltammetry curves of high-entropy alloy thin films in 1.0 M KOH electrolyte. Detailed Implementation
[0034] The present invention will now be described in further detail.
[0035] Example 1
[0036] (1) Preparation of (FeCoNiCr) 80 Pt 20 The preparation process of high-entropy alloy thin films is as follows:
[0037] ① Weigh high-purity Fe, Co, Ni, Cr, and Pt particles according to their atomic molar percentage content, and remelt the alloy ingot at least 4 times under the protection of a high-purity argon atmosphere using an electric arc melting method to ensure uniform alloy composition, thus obtaining (FeCoNiCr). 80 Pt 20 Button-shaped alloy ingot;
[0038] ② The obtained master alloy ingot is cut into Φ17*2mm pieces and polished until the surface is smooth to obtain (FeCoNiCr). 80 Pt 20 The target material was prepared by using 1.2*1.2mm conductive carbon paper as the substrate. Plasma was generated by bombarding the target material with a 1064nm laser beam under a high-purity argon atmosphere and depositing for 15 minutes to obtain (FeCoNiCr) loaded on the conductive substrate. 80 Pt 20 High-entropy alloy thin films.
[0039] (2) Regarding the above (FeCoNiCr)80 Pt 20 The high-entropy alloy thin film is subjected to electrochemical etching, and the process is as follows:
[0040] ① Dealloying treatment: A constant potential method was used with a 0.5M H2SO4 solution as the electrolyte. The working electrode, reference electrode, and counter electrode were a high-entropy alloy thin film, a calomel electrode, and a graphite carbon rod, respectively. The dealloying voltage was fixed at 0.98V (vs. SCE), and the dealloying time was adjusted from 0 to 1200s to explore the optimal dealloying conditions.
[0041] ② Washing and drying: The washing media are deionized water and anhydrous ethanol. The washing is performed 3 times. After natural drying at room temperature, (FeCoNiCr) is obtained. 80 Pt 20 High-entropy alloy thin-film catalytic materials.
[0042] Figure 1 The GIXRD pattern of the original alloy thin film shows that the film has a single-phase face-centered cubic structure; from Figure 1 (FeCoNiCr) can be observed. 80 Pt 20 As etching time increases, the high-entropy alloy film retains its face-centered cubic structure.
[0043] Figure 2 For different etching times (FeCoNiCr) 80 Pt 20 SEM images of the high-entropy alloy thin film are shown. (a) and (b) are the surface and cross-sectional scan morphologies of the original high-entropy alloy thin film, respectively. (c), (d), and (f) are the surface scan morphologies of the high-entropy alloy thin film after etching for 150 s, 300 s, and 800 s, respectively. (e) is the cross-sectional scan morphology of the high-entropy alloy thin film after etching for 300 s. It can be seen that the original high-entropy alloy thin film has a rough surface and a large specific surface area. After etching, the surface roughness of the high-entropy alloy thin film does not change significantly. The cross-sectional image shows that the high-entropy alloy thin film has a uniform thickness.
[0044] Figure 3 Original (FeCoNiCr) 80 Pt 20 TEM and SAED images of the high-entropy alloy thin film, (a) and (b) are high-resolution and SAED images of the original high-entropy alloy thin film, respectively, showing that the original alloy thin film has a face-centered cubic polycrystalline structure, which is consistent with the XRD results.
[0045] Figure 4 For etching (FeCoNiCr) after 300s 80 Pt 20TEM images and vacancy analysis diagrams of high-entropy alloy thin films are shown. Image (a) is a high-resolution transmission image of the high-entropy alloy thin film after etching for 300 s. Bright Pt atoms are randomly distributed in the solid solution lattice, and abundant atomic vacancies exist on the surface of the etched alloy film. Further visualization of the pixel intensity in the area within the dashed box is shown in image (b). The differences in pixel intensity allow for qualitative analysis of vacancies and elemental types. High pixel intensity indicates Pt atoms, low pixel intensity indicates vacancies, and elements in between are 3d transition metals such as Fe, Co, Ni, and Cr. Furthermore, the interplanar spacing of the alloy thin film fluctuates significantly after etching, ranging from [range missing]. This indicates the presence of significant lattice strain.
[0046] Figure 5 For the original and etched (FeCoNiCr) samples after 300s. 80 Pt 20 GPA images of high-entropy alloy films, Figure (a) shows that there is no obvious lattice strain in the original high-entropy alloy film, but significant lattice strain is generated after etching, as shown in Figure (b).
[0047] Experiment 1: Comparison of alkaline HER performance of high-entropy alloy thin films before and after electrochemical etching
[0048] Before and after electrochemical etching (FeCoNiCr) 80 Pt 20 The alkaline HER performance of the high-entropy alloy thin film was tested. The test procedure was as follows: a three-electrode system was used, where the working electrode was the high-entropy alloy thin film prepared in Example 1, the counter electrode was a graphite electrode, the reference electrode was a saturated calomel electrode, and the electrolyte was a 1.0M KOH solution. Linear sweep voltammetry was used with a scan rate of 5 mV / s. -1 The stability of alkaline HER was tested using an assembled flow-through anion exchange membrane electrolyzer. The test procedure is as follows: a two-electrode system was used, with the cathode being (FeCoNiCr). 80 Pt 20 The high-entropy alloy thin film has an IrO2 powder catalyst supported on carbon paper as the anode and a 1.0M KOH solution as the electrolyte.
[0049] Figure 6 To etch (FeCoNiCr) at different times 80 Pt 20 The linear sweep voltammetry curve of the alkaline HER of a high-entropy alloy thin film is shown in the figure. As can be seen from the figure, at a current density of 10 mA / cm²... -2 At that time, etching for 300s (FeCoNiCr) 80 Pt 20 The HER overpotential of the high-entropy alloy thin film was 18 mV, lower than the 90 mV before etching, indicating that electrochemical etching can significantly improve the alkaline HER catalytic activity of the sample. At a current density of 1 A / cm²,-2 At that time, (FeCoNiCr) was etched for 300 seconds. 80 Pt 20 The high-entropy alloy thin film HER overpotential is 104mV, which is lower than 336mV before etching. It exhibits excellent high-current-density alkaline HER catalytic performance. The specific overpotential values are shown in Table 1.
[0050] Figure 7 The etching depth for 300 seconds (FeCoNiCr) in Example 1 is [missing information]. 80 Pt 20 When high-entropy alloy thin films are used as HER catalysts in water electrolysis, they achieve a 10 mA / cm² reaction in a 1.0 M KOH electrolyte. -2 and 100mAcm -2 For comparison, the chronovoltage curve was used to test the 100 mA / cm² of commercial Pt / C in 1.0 M KOH electrolyte. -2 Chrono-voltage curves show that the overpotential of the 300s-etched high-entropy alloy film remained stable during the 58h alkaline HER stability test, indicating excellent sample stability. In contrast, the performance of the Pt / C powder catalyst deteriorated significantly after 10 hours of use.
[0051] Figure 8 For etching 300s (FeCoNiCr) 80 Pt 20 Chronovoltaic (ChRV) curves of alkaline HER were tested in an assembled flow-through anion exchange membrane electrolyzer. The left inset shows the ChRV curve of the noble metal electrode system under the same conditions, while the right inset shows a diagram of the actual assembled flow-through anion exchange membrane electrolyzer. Figure 8 As can be seen, the high-entropy alloy film etched for 300 seconds maintained a stable potential during the 20-day stability test, increasing by only 0.3V. In contrast, the energy consumption of the noble metal Pt / C||IrO2 system increased to 150% of its initial value after only 13 hours of operation.
[0052] Experiment 2: Comparison of acidic HER performance of high-entropy alloy thin films before and after electrochemical etching
[0053] Before and after electrochemical etching (FeCoNiCr) 80 Pt 20 The acidic HER performance of the high-entropy alloy thin film was tested. The test procedure was as follows: A three-electrode system was used, where the working electrode was the high-entropy alloy thin film prepared in the example, the counter electrode was a graphite electrode, the reference electrode was a saturated calomel electrode, and the electrolyte was a 0.5M H2SO4 solution. Linear sweep voltammetry was used, with a scan rate of 5 mV / s. -1 .
[0054] Figure 9 To etch (FeCoNiCr) at different times80 Pt 20 The linear sweep voltammetric curve of acidic HER for high-entropy alloy thin films, by Figure 9 It can be seen that at a current density of 10 mA cm⁻¹ -2 At that time, etching for 300s (FeCoNiCr) 80 Pt 20 The HER overpotential of the high-entropy alloy thin film was 46 mV, lower than the 54 mV before etching, indicating that electrochemical etching can significantly improve the acidic HER catalytic activity of the sample. At a current density of 1 A / cm²... -2 At that time, etching for 300s (FeCoNiCr) 80 Pt 20 The high-entropy alloy thin film HER overpotential is 106mV, which is lower than 139mV before etching. It exhibits excellent high current density acidic HER catalytic performance. The specific overpotential values are shown in Table 1.
[0055] Figure 10 For etching 300s (FeCoNiCr) 80 Pt 20 Chrono-voltage curves of acidic HER on high-entropy alloy thin films. It can be seen that the overpotential of the high-entropy alloy thin film etched for 300 s remained stable during the 24-hour acidic HER stability test, indicating excellent sample stability.
[0056] Experiment 3: Comparison of neutral HER performance of high-entropy alloy films before and after electrochemical etching
[0057] Before and after electrochemical etching (FeCoNiCr) 80 Pt 20 The neutral HER performance of the high-entropy alloy thin film was tested as follows: A three-electrode system was used, with the working electrode being the high-entropy alloy thin film prepared in the example, the counter electrode being a graphite electrode, and the reference electrode being a saturated calomel electrode. The electrolyte was 1.0M PBS solution. Linear sweep voltammetry was used, with a scan rate of 5 mV / s. -1 .
[0058] Figure 11 To etch (FeCoNiCr) at different times 80 Pt 20 The neutral HER linear sweep voltammetry curve of the high-entropy alloy thin film is shown in the figure. As can be seen from the figure, at a current density of 100 mA / cm²... -2 At that time, etching for 300s (FeCoNiCr) 80 Pt 20 The HER overpotential of the high-entropy alloy thin film was 175 mV, which was lower than 263 mV before etching. This indicates that electrochemical etching can significantly improve the neutral HER catalytic activity of the sample. The specific overpotential values are shown in Table 1.
[0059] Figure 12For etching 300s (FeCoNiCr) 80 Pt 20 Neutral HER chronovoltage curve of high-entropy alloy thin film. It can be seen that the overpotential of the high-entropy alloy thin film etched for 300s remained stable during the 24h neutral HER stability test, indicating that the sample has excellent stability.
[0060] Table 1 Comparison of overpotentials in the hydrogen evolution reaction of high-entropy alloy thin film catalysts after etching at different times.
[0061]
[0062] Overpotential η is in mV; §: Current density j is in mA / cm². -2 .
[0063] Example 2
[0064] (1) Preparation of (FeCoNiCr) 80 Pt 20 The preparation process of high-entropy alloy thin films is as follows:
[0065] ① Weigh high-purity Fe, Co, Ni, Cr, and Pt particles according to their atomic molar percentage content, and remelt the alloy ingot at least 4 times under the protection of a high-purity argon atmosphere using an electric arc melting method to ensure uniform alloy composition, thus obtaining (FeCoNiCr). 80 Pt 20 Button-shaped alloy ingot;
[0066] ② The obtained master alloy ingot is cut into Φ17*2mm pieces and polished until the surface is smooth to obtain (FeCoNiCr). 80 Pt 20 The target material was prepared by using 1.2*1.2mm conductive carbon paper as a substrate. Plasma was generated by bombarding the target material with a 1064nm laser beam under a high-purity argon atmosphere and depositing for 20 minutes to obtain (FeCoNiCr) loaded on the conductive substrate. 80 Pt 20 High-entropy alloy thin films.
[0067] (2) Regarding the above (FeCoNiCr) 80 Pt 20 The high-entropy alloy thin film is subjected to electrochemical etching, and the process is as follows:
[0068] ① Selection of dealloying voltage: The polarization curves of the original high-entropy alloy thin film were tested in a three-electrode system. The electrolyte was 0.5M H2SO4 solution. The working electrode, reference electrode, and counter electrode were the high-entropy alloy thin film, the calomel electrode, and the graphite carbon rod, respectively. The polarization curves of the high-entropy alloy thin film were tested in this system with a voltage range of -1.5 to 2.0V (vs. SCE).
[0069] ② Dealloying treatment: A constant potential testing method was used, with a 0.5M H2SO4 solution as the electrolyte. The working electrode, reference electrode, and counter electrode were a high-entropy alloy thin film, a calomel electrode, and a graphite carbon rod, respectively. The dealloying voltage was adjusted to -0.245-1.40V (vs. SCE), and the dealloying time was fixed at 500s.
[0070] ③ Washing and drying: The washing media are deionized water and anhydrous ethanol. The washing is performed 3 times. After natural drying at room temperature, (FeCoNiCr) is obtained. 80 Pt 20 High-entropy alloy thin-film catalytic materials.
[0071] Figure 13 The figure shows the polarization curves of the high-entropy alloy thin film in 0.5M H2SO4 solution. The dealloying voltages were selected based on these curves, as shown by the dots in the figure, which are -0.245V, 0.98V, and 1.40V, respectively.
[0072] Experiment 1: Comparison of alkaline HER performance of high-entropy alloy thin films before and after electrochemical etching at different potentials
[0073] Before and after electrochemical etching (FeCoNiCr) 80 Pt 20 The alkaline HER performance of the high-entropy alloy thin film was tested as follows: A three-electrode system was used, with the working electrode being the high-entropy alloy thin film prepared in Example 2, the counter electrode being a graphite electrode, and the reference electrode being a saturated calomel electrode. The electrolyte was a 1.0 M KOH solution. Linear sweep voltammetry was used, with a scan rate of 5 mV / s. -1 .
[0074] Figure 14 Etching (FeCoNiCr) for the same time at different potentials. 80 Pt 20 The linear sweep voltammetry curve of the alkaline HER of the high-entropy alloy thin film is shown in the figure. As can be seen from the figure, at a current density of 100 mA / cm²... -2 (FeCoNiCr) etched at a potential of 0.98V (vs. SCE) 80 Pt 20 The HER overpotential of the high-entropy alloy thin film was 54 mV, which was lower than 154 mV before etching and other etching potential conditions. The overpotentials were -0.245 V: 101 mV and 1.40 V: 93 mV, indicating that excellent alkaline HER catalytic activity could be obtained by etching in the potential range of 0.98 V (vs. SCE).
Claims
1. A high-entropy alloy catalytic material for hydrogen evolution in water electrolysis, characterized in that, The invention includes a conductive substrate material and a high-entropy alloy thin film deposited on the surface of the conductive substrate material; the high-entropy alloy thin film has the chemical formula (FeCoNiCr) based on the molar percentage of each atom. 100-x Pt x , where 10≤x≤40.
2. A method for preparing the high-entropy alloy electrolytic water evolution hydrogen evolution catalyst material according to claim 1, characterized in that, Includes the following steps: (1) Weigh the Fe, Co, Ni, Cr and Pt metal raw materials according to the molar percentage of each atom; (2) The metal raw materials from step (1) are subjected to electric arc melting to obtain (FeCoNiCr). 100-x Pt x The alloy ingot is cut and its surface is polished to obtain (FeCoNiCr). 100-x Pt x Target material; (3) Utilization (FeCoNiCr) 100-x Pt x The target material (FeCoNiCr) was deposited on a conductive substrate using pulsed laser deposition. 100-x Pt x High-entropy alloy thin films; (4) The obtained high-entropy alloy film is electrochemically etched, washed and dried to obtain the high-entropy alloy water electrolysis hydrogen evolution catalyst material.
3. The preparation method of the high-entropy alloy electrolysis water evolution hydrogen catalytic material according to claim 2, characterized in that, In step (4), electrochemical etching is performed using a constant potential etching method, with an applied voltage of -0.245-1.40 V (vs. SCE) and an etching time of 0-1200 s.
4. The preparation method of the high-entropy alloy electrolytic water evolution hydrogen evolution catalyst according to claim 2, characterized in that, In step (4), the electrochemical etching temperature is room temperature.
5. The preparation method of the high-entropy alloy electrolytic water evolution hydrogen evolution catalyst according to claim 2, characterized in that, In step (4), the medium for electrochemical etching is an acidic solution.
6. The preparation method of the high-entropy alloy electrolysis water evolution hydrogen catalytic material according to claim 5, characterized in that, In step (4), the acidic solution is at least one of H2SO4, HNO3, and HCl.
7. The preparation method of the high-entropy alloy electrolysis water evolution hydrogen catalytic material according to claim 2, characterized in that, In step (3), the substrate size used in the pulsed laser deposition method is Φ5-12 mm.
8. The preparation method of the high-entropy alloy electrolytic water evolution hydrogen evolution catalyst according to claim 2, characterized in that, In step (3), the deposition time for pulsed laser deposition is 10-20 min.
9. The preparation method of the high-entropy alloy electrolysis water evolution hydrogen catalytic material according to claim 2, characterized in that, In step (2), argon is used as the protective atmosphere in the electric arc melting method.
Citation Information
Patent Citations
Six-element high-entropy foam for hydrogen production through hydrolysis and preparation method of six-element high-entropy foam
CN114836780A
Catalyst for producing hydrogen through large-current electro-catalysis water decomposition as well as preparation method and application of catalyst
CN114855187A